Antara Hitam dan Putih: Penghulu pada Masa Kolonial Belanda - Fauzia, Amelia (Studia Islamika, 2003)
As indicated in the title, this book describes position of the pangulu as a social phenomenon in the period of Dutch colonial administration when many social and religious changes took place. There are three main focuses of the book in describing the role of the pangulu; first, to examine their history and structure in the colonial government; second, to describe their conflicting roles as Islamic leaders and as colonial government officials; and third, to understand how pangulu interacted with Islamic reformism and the nationalist movement.DOI: 10.15408/sdi.v10i2.634